Nitrification Inhibitor 3,4-Dimethylpyrazole Phosphate Application During the Later Stage of Apple Fruit Expansion Regulates Soil Mineral Nitrogen and Tree Carbon–Nitrogen Nutrition, and Improves Fruit Quality - Wang, Fen; Xu, Xinxiang; Jia, Zhihang; Hou, Xin; Chen, Qian; Sha, Jianchuan; Liu, Zhaoxia; Zhu, Zhanling; Jiang, Yuanmao; Ge, Shunfeng (Frontiers in Plant Science, 2020)
In order to solve the problems of nitrogen (N) losses and fruit quality degradation caused by excessive N fertilizer application, different dosages of the nitrification inhibitor, 3, 4-dimethylpyrazole phosphate (DMPP) (0, 0.5, 1, 2, and 4 mg kg-1 soil), were applied during the later stage of ‘Red Fuji’ apple (Malus domestica Borkh.) fruit expansion in 2017 and 2018. The effects of DMPP on soil N transformation, carbon (C)-N nutrition of tree, and fruit quality were investigated. Results revealed that DMPP decreased the abundance of ammonia-oxidizing bacteria (AOB) amoA gene, increased the retention of NH4+-N, and decreased NO3--N concentration and its vertical migration in soil. DMPP reduced 15N loss rates and increased 15N residual and recovery rates compared to the control. 13C and 15N double isotope labeling results revealed that DMPP reduced the capacity of 15N absorption and regulation in fruits, decreased 15N accumulation in fruits and whole plant, and increased the distribution of 13C from vegetative organs to fruits. DMPP increased fruit anthocyanin and soluble sugar contents, and had no significant effect on fruit yield. The comprehensive analysis revealed that the application of 1 mg DMPP kg-1 soil during the later stage of fruit expansion effectively reduced losses due to N and alleviated quality degradation caused by excessive N fertilizer application.